Differing six minute pacing strategies affect anaerobic contribution, oxygen uptake, muscle deoxygenation and cycle performance - Murray, J.; McCrudden, M.; Murias, J. M.; Nolte, V.; Belfry, G. R. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: This study compared an all-out start (AO) to a constant power start strategy (CON) during a 6 min cycle performance on utilization of W´ (energy above critical power [CP]), muscle deoxygenation (HHb), oxygen uptake (VO2) and performance in recreationally active individuals. The AO strategy was similar to that employed by rowers.